Analysis of Room Ventilation, Clean and Healthy Living Behavior with Upper Respiratory Tract Infection Incidence - Agus Aan Adriansyah; Amanatul Istifaiyah; Dwi Handayani (Universitas Airlangga, 2021)
Background: Upper Respiratory Tract Infection (URI) is often experienced by Islamic boarding school students, who experience 30% of total reported URIs. This high incidence of URI can be caused by ventilation in students’ rooms not meeting health requirements and poor implementation of Clean and Healthy Living Behavior (CHLB). Purpose: This study aims to analyze the risk level of ventilation and CHLB as pertains to URI incidence among Amanatul Ummah Surabaya Islamic Boarding School students. Methods: This research used an analytic survey design with a cross-sectional approach. The study population was 853 students. The sampling method used was proportionate stratified random sampling, yielding a sample of 207 students. Samples were taken through drawing the number of absences. The data were obtained by interviews utilizing CHLB questionnaires, field observation of ventilation, and observation of respondent’s medical records to obtain information on the history of the URI. The data was analyzed via chi-square test (α=0.05). Results: Respondents with room ventilation that did not fulfil requirements tended to experience URI 11.13 times more frequently than respondents with room ventilation that fulfilled the requirements, while respondents with poor CHLB tended to experience URI 7.15 times more often than respondents with good CHLB. The more ventilation did not fulfil the requirements and the poorer the implementation of CHLB, the more respondents tended to experience URI. Conclusion: The leader of Amanatul Ummah Surabaya Islamic boarding school was expected to be able to evaluate the construction of boarding schools, particularly with regard to ventilation, to fulfil the applicable health requirements and provide adequate CHLB facilities.